Stimulation of Plasmin Catalyzed Conversion of SingleChain to Two-Chain Urokinase-Type Plasminogen Activator by Sulfated Polysaccharides - Rydzewski, Andrzej; Takada, Yumiko; Takada, Akikazu (Thrombosis and Haemostasis, 1989)
Influence of heparin, chondroitin sulfate C and dextran sulfate (MW 3,500 and 7,000) on plasmin catalyzed conversion of singlechain (scu-PA) to two-chain (u-PA) urokinase-type plasminogen activator and generation of plasmin in mixtures of scu-PA and Glu-plasminogen (Glu-plg) was investigated. Conversion of scu-PA to u-PA catalyzed by plasmin was enhanced by chondroitin sulfate C and heparin, maximally by 10-fold and 3-fold, respectively. Sulfated polysaccharides potentiated generation of plasmin in mixtures of Glu-plg and scu-PA, as well as enhanced plasminogenolytic activity of u-PA. The possible role of these interactions is discussed.
Keywords: Single-chain urokinase-type plasminogen activator; Two-chain urokinase-type plasminogen activator; Sulfated polysaccharides; Potentiation